Development and Validation of TLC of Flavonoid from the Ethanolic Extract of Plant Enhydra fluctuans - Pahari, Sandip Kumar; Panda, Shambo; Manna, Sourav; Mukhopadhyaya, Projjal; Mahato, Ujjal; Biswal, Bishnupada (Journal of Drug Delivery and Therapeutics, 2021)
Thin layer chromatography is a technique or an analytical tool to separate the bioactive compound from the mixture of components. In current research work special attention was given to develop specific solvent system and to validate the principle of separation of Flavonoid. The ethanolic extract of plant namely Helencha (in Bengali) was selected for such purpose. After several trials, the presence of Flavonoid which was confirmed by qualitative evaluation and was sepahjvvrated successfully under this study and the process was validated under the circumstances of ICH Guideline. The plant not only contained Flavonoid but there were the presence of little quantity of Alkaloid, Saponin and Tannins also. Due to presence of Flavonoid the ethanolic fraction of the plant may be evaluated for Anti-inflammatory and Anthelmintic activity for further research. The plant Helencha is known as Enhydra fluctuans belongs to the family Astereceae. According to folklore claim the plant is useful for nutrition purpose. Not only that the plant is also useful in Dropsy, anasarca and snake bite. As per the literature survey, the plant has Antioxidant and Analgesic activity. Here the total attention was given to separate Flavonoid from the mixture of Components present in the ethanolic fraction of the leaves of the plant. Keywords: Flavonoid, Alkaloid, ICH Guideline, Enhydra fluctuans, Dropsy, Anaasrca.